DETERMINATION OF THE COINCIDENCE CORRECTION FACTOR ON MEASURING SEMICONDUCTOR DETECTOR EXPERIMENTAL EFFICIENCY - Trịnh , Văn Cường; Trần , Tuấn Anh; Hồ , Mạnh Dũng; Hồ , Văn Doanh; Nguyễn , Thị Thọ; Hà , Anh Tú (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2020)
The efficiency is an important factor in measuring the semiconductor detector which directly impacts to experimental results of Instrumental neutron activation analysis. The efficiency curve was determined by standard source measurements including Cd-109, Cs-137, Mn-54, Co-60, Eu-152, Ba-133. However, corresponding to a multi-energy radioisotope that emits more two gammas, the coincidence effect appears when both gammas having the same direction arrive at the volume of the detector in the resolution of the spectrometer. The coincidence effect is clearer on a closer distance, so the efficiency is more significantly different than the correct value. In this paper, the coincidence effect is researched and calculated at four positions as well as verified at three positions from the detector window.